Going green in stages: Psychological processes behind intention formation and action for climate mitigation - Ylva Andersson; Shane Timmons; Maria Lee; Pete Lunn (The Economic and Social Research Institute (ESRI), 2024)
Mitigating the climate crisis requires changes to policy, business, and consumer behaviour in favour of sustainability. For consumers, use of private motor vehicles and consumption of meat and dairy are high-impact behaviours. To assist behaviour change, it is useful to understand where in the process of change people currently are and what motivates the next step. In a pre-registered study using a representative sample of adults (N = 1200), we measure "stage of change" for transport and diet behaviours, then test the relationship between stage of change and a battery of psychological variables informed by previous theoretical and empirical research. Our modelling approach allows us to test whether the variables associated with change depend on the stage an individual is moving to and from. The models reveal that, for both transport and dietary behaviours, people who intend to change worry more about climate change and feel more morally responsible to act than people who see no need to change. Acting on intentions is associated with holding a strong environmental identity. We also find differences between the two behaviours in the variables associated with stage of change. For example, positive environmental attitudes predict intentions and actions only for transport behaviour, whereas belief in the effectiveness of collective action predicts intention to change diet. Sociodemographic predictors of change also differ between behaviours: urban dwellers are more likely to act on transport intentions, while being a woman predicts intentions and action for dietary change. Other psychological variables cited in the literature have little association with change, including social norms and belief in individual responsibility. The results show the benefit of conceptualising behaviour change as a multi-stage process.
Keywords: 330; climate change; stage of change; intention-action gap; transport; diet